TERDAPAT HUBUNGAN ANTARA PENGETAHUAN DAN SIKAP MASYARAKAT PADA PROGRAM VAKSINASI COVID-19 - Akub Selvia; Betty Betty (Poltekkes Kemenkes Aceh, 2023)
The COVID-19 outbreak has now become a global pandemic for all countries since it was announced by WHO which was first reported on December 31, 2019 and is still endemic in the world. Covid-19 was first discovered in Wuhan, Hubei Province of China. Data from the Ministry of Health in 2021 daily cases of COVID-19 in Indonesia on January 29 reached 1,051,795 confirmed cases of COVID-19 with 29,518 deaths. The purpose of this study was to determine the relationship between the level of knowledge and public attitudes towards the Covid-19 vaccination program at the Maja Sector Police. Methods This research is a quantitative study with a cross-sectional method using primary data (questionnaire). The population in this study was 59,705 respondents using probability sampling technique with simple random sampling using the Slovin formula so that the research sample was 100 respondents. Data analysis used Spearman rank with a significance level of p-velue <0.05. The results of this study indicate that the highest age is in the late adult category (36-45 years) with a total of 31 respondents (31%), and the highest gender is in the female category, which is 59 respondents (59%), then the highest level of education is in the high school category. amounted to 64 respondents (64%), and a good level of knowledge amounted to 57 respondents (57%), and also attitudes that had a good category were 52 respondents (52%). The conclusion based on the results of the Spearman, s rho statistical test with the help of SPSS 26 obtained a correlation coefficient or rho of 0.781 with a sign value or p-velue of 0.000 which means Ho is rejected and Ha is accepted, because the value is 0.000 <0.05. So it can be concluded that there is a relationship between the level of knowledge and attitudes towards the covid-19 vaccination program at the Maja Sector Police.